Modeling Effects on Forces in Shear Wall-Frame Structures* - Surahman, Adang (ITB Journal Publisher, LPPM ITB, 2015)
Shear walls are added to a structural system to reduce lateral deformations in moment resisting frames and are designed to carry a major portion of lateral load induced by an earthquake. A small percentage error in the shear wall calculation will have a significant effect on the frame forces. The results show that even a slight difference in structural assumption, or modeling, results in significant differences. Some of these differences are beyond the values that are covered by safety factors for errors in modeling. The differences are more obvious in the upper stories. It is not recommended to overestimate shear wall stiffness, nor underestimate frame stiffness.